Effects of grazing intensity on plant richness and diversity: a meta‐analysis - Herrero‐Jáuregui, Cristina; Oesterheld, Martín (Oikos, 2018)
Most of our knowledge of the effect of grazing on grassland structure is based on grazed–ungrazed contrasts. The effects of grazing in the most common scenario, where grazing intensity varies from low to high grazing intensity, are less known. The objectives of this paper were to 1) quantify the effect of stocking rates on species richness and diversity of grasslands world‐wide, and 2) evaluate the response under different environmental and experimental conditions. We conducted a meta‐analysis of experiments with at least two levels of controlled stocking rates and evaluated their effect on species richness and diversity. The results showed that the response of richness and diversity to either reducing or increasing stocking rate from a moderate level mostly fell within the range  25% or  5 species. Mean response of species richness and diversity to increasing stocking rate from moderate to high levels was negative. Mean response to lowering stocking rate from moderate levels was not different from zero. However, overall, species richness significantly decreased as stocking rate increased. The response of richness and diversity to stocking rate was not related to mean precipitation, productivity or aridity. However, the most negative responses of richness to stocking rate were larger in arid, low productivity systems than in subhumid and humid systems. The effects of grazing on richness and diversity found in this review were smaller than the effects on species composition shown by the literature. Thus, grazing drastically changes species composition, but the net change of species and diversity is much smaller.